(untitled) (Eurasian Research Bulletin, 2023)
The development of ways to reduce the cost of feed rations can be solved by expanding the range of input components through the use of secondary products of the food industry. In the Republic of Uzbekistan, silkworm waste belongs to the above components for obtaining substances that increase productivity. These include chitosan obtained from chitin by deacetylation with varying degrees. Results have been obtained that indicate efficiency compared to diets currently used in industrial and vivarium conditions.